Peningkatan Efektivitas Manajemen Kesehatan Melalui Implementasi Teknologi Informasi - Jimmy Triputra; Nurhayati Nurhayati; Risda Choirunisa; Tria Pamungkasari; Vip Paramata (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to evaluate the impact of information technology implementation in healthcare management. By analyzing data from the periods before and after implementation, we identified significant changes in operational efficiency and healthcare service quality. The findings of this research provide valuable insights for healthcare organizations to optimize their management. The implementation of information technology has positively contributed to operational efficiency. Administrative processes and inventory management have seen a 20% increase in efficiency, creating a more effective and organized environment. Furthermore, data analysis also indicates a decrease in response time to patient needs, enhancing the overall responsiveness of healthcare services. Insights gained from this research can assist healthcare organizations in identifying areas for improvement in their management. By understanding the positive impact of information technology implementation, organizations can take strategic steps to enhance operational performance and improve the patient experience.